Characterizing the Acoustic Behavior of Hexagonal Periodic Cellular Cores - Ahmed, Ammar (2020)
A Master of Science thesis in Mechanical Engineering by Ammar Ahmed entitled, “Characterizing the Acoustic Behavior of Hexagonal Periodic Cellular Cores”, submitted in December 2020. Thesis advisor is Dr. Maen Alkhader and thesis co-advisor is Dr. Bassam Abu-Nabah. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).